Alleviating poverty in rural Nigeria - Obine, C.P.O. (1999)
Like many developing countries, rural poverty is a widespread phenomenon in Nigeria. Various policies and programmes have been designed and implemented towards alleviating rural poverty in Nigeria. The paper advocates for an integrated approach for rural development, which would ensure empowerment and increased participation of rural people in the development process, and also to provide a wide range of choices of techniques for ensuring the rapid elimination of rural poverty. - Reproduced
Keywords: Poverty - Nigeria; Poverty